Significantly higher procalcitonin levels could differentiate Gram-negative sepsis from Gram-positive and fungal sepsis - Brodská, Helena; Malíčková, Karin; Adámková, Václava; Benáková, Hana; Šťastná, Markéta Marková; Zima, Tomáš (Clinical and experimental medicine, 2013)
Procalcitonin (PCT) levels can distinguish between infectious and non-infectious systemic inflammatory response. However, there are some differences between Gram-negative (G-), Gram-positive (G+), and fungal bloodstream infections, particularly in different cytokine profiles, severity and mortality. The aim of current study was to examine whether PCT levels can serve as a distinguishing mark between G+, G-, and fungal sepsis as well. One hundred and sixty-six septic patients with positive blood cultures were examined on C-reactive protein (CRP) and PCT on the same date of blood culture evaluation. The median (interquartile range, IQR) of CRP and PCT in G+, G-, and fungal cohorts and comparison of measured values between groups were made using the Kruskal-Wallis test with subsequent Bonferroni's corrections, with p < 0.05. In 83/166 (50 %) of blood cultures, G+ microbes, 78/166 (47 %) G- rods, and 5/166 (3 %) fungi were detected. PCT concentrations (ng/ml) were significantly higher in G- compared to other cohorts: 8.90 (1.88; 32.60) in G-, 0.73 (0.22; 3.40) in G+, and 0.58 (0.35; 0.73) in fungi (p < 0.00001). CRP concentrations did not differ significantly in groups. Significantly higher PCT levels could differentiate G- sepsis from G+ and fungemia. In contrast to CRP, PCT is a good discriminative biomarker in different bloodstream infections.
Keywords: Sepsis; retrospektivní studie; Humans; peptid spojený s genem pro kalcitonin; diferenciální diagnóza; Calcitonin Gene-Related Peptide; lidé středního věku; sepse; Middle Aged; proteinové prekurzory; mužské pohlaví; kalcitonin; Diagnosis, Differential; grampozitivní bakteriální infekce; gramnegativní bakteriální infekce; Calcitonin; mykózy; biologické markery; C-reaktivní protein; ženské pohlaví; lidé; C-Reactive Protein; Gram-Negative Bacterial Infections; Mycoses; Protein Precursors; Biomarkers; Aged; senioři; Male; Retrospective Studies; Gram-Positive Bacterial Infections; Female